Optimizing Solo Athletic Excellence: Analyzing Psychological, Economic, and Cultural Drivers in Elite Sports Performance - Dilip Singh Songara (Recent Trends in Sports, 2024)
This research paper explores the multifaceted drivers behind elite solo sports performance, integrating psychological, economic, and cultural perspectives to understand how these factors contribute to athletic excellence. The study synthesizes insights from a variety of academic journals, authoritative books in sports science, and articles from prominent sports and psychology magazines. Through a mixed-methods approach, we analyze the resilience and mental strategies employed by solo athletes, assess the economic conditions that enable or hinder their training and performance, and evaluate the cultural support systems that influence their career trajectories. Our findings reveal that while psychological preparedness is critical, it is profoundly influenced by the athlete's economic conditions and the cultural context within which they operate. The results contribute to a deeper understanding of the holistic environment needed to nurture and optimize solo athletic excellence. Recommendations are provided for stakeholders, including sports organizations and coaching professionals, to enhance the support structures and resources available to solo athletes. This paper fills a significant gap in contemporary sports performance research by providing a comprehensive analysis of the interplay between the mind, economic support, and cultural factors in the realm of elite sports. This abstract aims to capture the essence of our research, emphasizing the interdisciplinary analysis and the unique insights derived from a broad spectrum of sources. It's designed to engage academic peers, sports professionals, and policymakers interested in the optimization of elite athletic performance.
Keywords: Solo athletic performance; cultural influence; economic factors; elite sports; psychological resilience